If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 9t + -3 = 9t + 26 + -5t Reorder the terms: 4 + -3 + 9t = 9t + 26 + -5t Combine like terms: 4 + -3 = 1 1 + 9t = 9t + 26 + -5t Reorder the terms: 1 + 9t = 26 + 9t + -5t Combine like terms: 9t + -5t = 4t 1 + 9t = 26 + 4t Solving 1 + 9t = 26 + 4t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-4t' to each side of the equation. 1 + 9t + -4t = 26 + 4t + -4t Combine like terms: 9t + -4t = 5t 1 + 5t = 26 + 4t + -4t Combine like terms: 4t + -4t = 0 1 + 5t = 26 + 0 1 + 5t = 26 Add '-1' to each side of the equation. 1 + -1 + 5t = 26 + -1 Combine like terms: 1 + -1 = 0 0 + 5t = 26 + -1 5t = 26 + -1 Combine like terms: 26 + -1 = 25 5t = 25 Divide each side by '5'. t = 5 Simplifying t = 5
| 4y+(-13z)+(-10y)+17z= | | 160-46+6=x | | -j=-20 | | -3+8n=15 | | 0.25x^2=0.5x+2 | | 67-7x=5x-17 | | b-10=62 | | 30000+2400y=36000+2000y | | ax-b:c=d;3x-5/2=2 | | p^2-4p-32=13 | | 3+5x-2x^2=0 | | 6ln(2x+6)=20 | | 57-28k=-7(4k-5) | | 4a^2+4a-35=0 | | 3x+5y+2x+-3y= | | 7+4x=2(-x-2)-5(6x+4) | | -82=j+-74 | | 4y^4-8xy^5=1 | | ax+6a=8b | | 8/5/13/15 | | 4j=-52 | | x^2-6x=10-3x | | f(12)=5-22 | | A/q-p/q=1 | | 0.5w-0.75=0.67w+2 | | 2=2/7y | | u/10=9 | | 6x-3=-5x-3 | | -2-10x=-2+6 | | z+-14=21 | | 9.4=3.5p-0.4 | | u-49=40 |